2014
DOI: 10.1037/a0034034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of professional status on perceptions of romantic relationship dynamics.

Abstract: Men and women who violate traditional expectations with regard to professional status are perceived negatively by others, and can face negative outcomes in the workplace. Here we examine whether these negative perceptions extend to observers' evaluations of status violators' intimate relation ships. We employed a fictional scenario depicting a heterosexual married couple, manipulating the professional status of each character while holding all other information constant. Participants (N = 396) projected lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…More generally, people have a stronger tendency to associate careers or leadership with men as compared to women (e.g., Koenig, Eagly, Mitchell, & Ristikari, 2011; Rudman & Killianski, 2000), and prefer that men occupy higher status roles than women (Hettinger, Hutchinson, & Bosson, 2014). The consequences of violating these expectations may be politically pernicious for women as backlash penalizes women (but not men) candidates for their power-seeking intentions (Okimoto & Brescoll, 2010).…”
mentioning
confidence: 99%
“…More generally, people have a stronger tendency to associate careers or leadership with men as compared to women (e.g., Koenig, Eagly, Mitchell, & Ristikari, 2011; Rudman & Killianski, 2000), and prefer that men occupy higher status roles than women (Hettinger, Hutchinson, & Bosson, 2014). The consequences of violating these expectations may be politically pernicious for women as backlash penalizes women (but not men) candidates for their power-seeking intentions (Okimoto & Brescoll, 2010).…”
mentioning
confidence: 99%
“…shows that men and women violating gender norms in the relationship domain also face negative evaluations (MacInnis & Baliga, 2019;Hettinger, Hutchinson, & Bosson, 2014). In two studies we show that the backlash as has been found in the work domain also provide an explanation why people negatively evaluate men and women who break with gender norms in the relationship domain.…”
Section: Discussionsupporting
confidence: 63%
“…Cross-class couples in which women earn more, are more highly educated or have a higher status occupation than the man were viewed negatively by others (MacInnis & Baliga, 2019). Compared to people in traditional relationships, in couples where the man has a lower status occupation than his female partner, people predict the male partner to be less satisfied with the relationship and report less sympathy with the female partner (Hettinger, Hutchinson, & Bosson, 2014)and can face negative outcomes in the workplace.…”
Section: Do the Mechanisms Of Status Violations Spill-over To Partner Dynamics?mentioning
confidence: 96%
See 1 more Smart Citation
“…When selecting multiple subsets of stimuli to assign to different experimental conditions, researchers often need to control for other relevant variables. For example, to carry out a study on gender stereotyping, Hettinger, Hutchinson, and Bosson (2014) needed to identify two sets of household chores from a longer list—one set to assign to a male character in a story, one to a female character—so that the chosen sets matched on genderedness, pleasantness, difficulty, and time consumption. This approach is used widely in studies of word recognition, the focus of this paper, and has also been used in a variety of other psychological research, including the relationship between race and face perception (Zebrowitz, White, & Wieneke, 2008), between attentional processing and obesity (Carters, Rieger, & Bell, 2015), and between emotion and memory (Schmidt, Patnaik, & Kensinger, 2011), among others.…”
Section: Introductionmentioning
confidence: 99%